The Relationship between Ventilation and Physical Quality of Houses with Pulmonary Tuberculosis Cases in the Working Area of Sragen Primary Healthcare Center, Sragen Regency - Radhika Wulandari; Budiyono Budiyono; Sulistiyani Sulistiyani; Nur Endah Wahyuningsih (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Pulmonary tuberculosis is ranked the second health problem in the world, including Indonesia with reasonably high mortality rates. This study examined the association between the ventilation, physical condition, and the prevalence of pulmonary tuberculosis in the working area of the Sragen Primary Healthcare Center. Methods: This study used a case-control design and purposive sampling to select 40 patients with positive smear pulmonary tuberculosis as the case group and 40 subjects with negative smear pulmonary tuberculosis as the control group who lived in the same area. Results and Discussion: Ventilation volume per hour (p = 0.007; OR = 3.889; 95% CI = 1.533–9.868), ventilation area (p = 0.014; OR = 3.462; 95% CI = 1.379–8.691), lighting intensity (p = 0.007; OR = 3.955; 95% CI = 1.546–10.114) and a humidity level (p = 0.001; OR = 5.762; 95% CI = 2.065–16.079) were associated with the prevalence of pulmonary tuberculosis in patients of the productive age group who attended the Sragen Primary Healthcare Center. The results of the multivariate analysis conclude that ventilation (OR = 5.900), humidity level (OR = 8.414), and occupancy density (OR = 0.113) had joint influences with a significant contribution of 41.3% to TB prevalence. Conclusion: House' ventilation and humidity are the main factors contributing to the incidence of pulmonary tuberculosis in the working area of Sragen Primary Healthcare Center.